Combination of the searches for pair-produced vectorlike partners of the third-generation quarks at √s=13 TeV with the ATLAS detector - Aaboud, Morad; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physical review letters, 2018)
A combination of the searches for pair-produced vectorlike partners of the top and bottom quarks in various decay channels (T→Zt/Wb/Ht, B→Zb/Wt/Hb) is performed using 36.1 fb−1 of pp collision data at √s=13 TeV with the ATLAS detector at the Large Hadron Collider. The observed data are found to be in good agreement with the standard model background prediction in all individual searches. Therefore, combined 95% confidence-level upper limits are set on the production cross section for a range of vectorlike quark scenarios, significantly improving upon the reach of the individual searches. Model-independent limits are set assuming the vectorlike quarks decay to standard model particles. A singlet T is excluded for masses below 1.31 TeV and a singlet B is excluded for masses below 1.22 TeV. Assuming a weak isospin (T,B) doublet and |VTb|≪|VtB|, T and B masses below 1.37 TeV are excluded.
M. Aaboud, A.E. Baas, A.E. Bolz, O. Brandt, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, M. Kolb, A. Kugel, M. Lisovyi, H. Meyer Zu Theenhausen, F. Napolitano, D.I. Narrias Villar, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, S.M. Weber, M. Wessels, X. Yue [und weitere] (ATLAS Collaboration)
Gesehen am 03.04.2019